2020
DOI: 10.3390/foods9050644
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Occurrence, Detection and Detoxification of Aflatoxins in Foods and Feeds

Abstract: Mycotoxin contamination continues to be a food safety concern globally, with the most toxic being aflatoxins. On-farm aflatoxins, during food transit or storage, directly or indirectly result in the contamination of foods, which affects the liver, immune system and reproduction after infiltration into human beings and animals. There are numerous reports on aflatoxins focusing on achieving appropriate methods for quantification, precise detection and control in order to ensure consumer safety. In 2012, the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 226 publications
(217 reference statements)
0
74
0
Order By: Relevance
“…Aflatoxins represent the most abundant mycotoxins found in foodstuffs, oilseeds, cereals, milk, soils, animals, and humans. All types of aflatoxins are derived from fungal species belonging to the genus Aspergillus and are considered among the most harmful mycotoxins for animals and humans [ 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. As mentioned above, in suckling piglets and growing, finished, and breeding pigs, the main biological effects of aflatoxins are carcinogenicity, immunosuppression, mutagenicity, teratogenicity, decreased feed efficiency and poor weight gain, impaired liver, and altered serum biochemical parameters [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins represent the most abundant mycotoxins found in foodstuffs, oilseeds, cereals, milk, soils, animals, and humans. All types of aflatoxins are derived from fungal species belonging to the genus Aspergillus and are considered among the most harmful mycotoxins for animals and humans [ 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. As mentioned above, in suckling piglets and growing, finished, and breeding pigs, the main biological effects of aflatoxins are carcinogenicity, immunosuppression, mutagenicity, teratogenicity, decreased feed efficiency and poor weight gain, impaired liver, and altered serum biochemical parameters [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin exposure contributed to the majority of liver cancer burden in 2005, second only to HBV and HCV. Aflatoxins are another important etiological factor of liver cancer in China, which have been classified as a Group 1 human carcinogen by the International Agency for Research on Cancer ( 27 ). Aflatoxins are produced primarily by the fungi Aspergillus flavus and Aspergillus parasiticus , which infect food crops such as maize, peanuts, groundnuts, and tree nuts ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxins are secondary metabolite products of Aspergillus species molds, and human exposure to these toxins occurs due to exposure to contaminated food such as grains, nuts, eggs, spices, milk, and meat in tropical countries of sub-Saharan Africa and southeast Asia [ 24 , 25 ]. Although aflatoxin contamination is common and a major problem in these countries, studies have shown that aflatoxin contamination is a global occurrence including in parts of Europe and the Americas [ 26 , 27 , 28 ]. AFB1 is the most toxic and common of all types of aflatoxins in human populations.…”
Section: Introductionmentioning
confidence: 99%